CRUDE MILK INDICATIVE PRICES: MECHANISM OF DEFINING AND APPLICATION - Shibaykin, Vladimir; Alexeyevna, Dolbilova Ekaterina (Economics of Agriculture, 2013)
In the article the results of the analysis of the environment of purchase prices of crude milk in Russia and the Saratov region, including their long-term dynamics of seasonal fluctuations are presented. Author’s calculations prove an exponential rise in prices and its negative influence on consumer prices of dairy production. Importance of monitoring of inter-branch parity of the agricultural and industrial prices is emphasized. Experience of use of indicative pricing within agreements between national associations of producers and milk processers is generalized. Special attention is given to methodical questions of justification of indication prices. The improvement guidelines «Temporary methodical recommendations on the organization of monitoring of the current profitability, indication prices and production costs of main types of agricultural production» are formulated. The offered author’s approach is approved on materials of the Saratov region. The corridor of the minimum and ceiling indication prices for 2013 is reasonable. The conclusion is drawn on the need of reconstruction of the regional Union of producers and milk processers Saratov-Molprom.